2012
DOI: 10.1083/jcb.201205169
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 promotes transendothelial migration of cancer cells through β1 integrin

Abstract: Cdc42 induces β1 integrin expression at the transcriptional level via the transcription factor SRF to promote cancer cell interaction with endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(193 citation statements)
references
References 44 publications
(69 reference statements)
7
179
2
5
Order By: Relevance
“…Migration of cancer cells through the endothelial lining of the blood vessels is a critical step of extravasation (39,40). To obtain more direct evidence for the contribution of E6AP to tumor cell extravasation, we measured their ability to cross an endothelial barrier using the transendothelial migration assay.…”
Section: E6ap Expression Impedes Tumor Cell Colonizationmentioning
confidence: 99%
“…Migration of cancer cells through the endothelial lining of the blood vessels is a critical step of extravasation (39,40). To obtain more direct evidence for the contribution of E6AP to tumor cell extravasation, we measured their ability to cross an endothelial barrier using the transendothelial migration assay.…”
Section: E6ap Expression Impedes Tumor Cell Colonizationmentioning
confidence: 99%
“…Cdc42 was initially identified as a mediator of cell polarity and division in Saccharomyces cerevisiae [24, 25]. Recent studies show that deregulation of Cdc42 is involved in the activation of many cellular cascades such as cell polarity, cytoskeleton remolding, proliferation, migration, adhesion membrane trafficking, and transportation, and leads to the development of many pathological disorders including cancers in humans [26-28]. Stimulation of the G-protein-coupled receptor kinase interacting protein 1 (GIT1)-Rac/Cdc42 axis is important for cell motility in NSCLC, and thus activating of Rac1/Cdc42 is critical for the GIT1-induced invasiveness of NSCLC [29].…”
Section: Discussionmentioning
confidence: 99%
“…It was initially identified in Saccharomyces cerevisiae as a cell-cycle mutant that contributed to the regulation of budding and mating projection (39). Previous studies have demonstrated that CDC42 is involved in cell proliferation, cell cycle progression, cytoskeletal remodeling, migration and invasion (40)(41)(42)(43). Consistent with its important functions in these distinct physiological and pathological processes, abnormal expression of CDC42 has been identified in numerous diseases, particularly in human cancer.…”
Section: Cdc42 Is Involved In Mir29a-induced Effects In Nsclc Cellsmentioning
confidence: 84%